Looking glass sound ebook - Ward, Catriona (2023)
A USA TODAY BESTSELLER Best Book of 2023 ( Vulture ) A Best Horror Book of All Time ( Cosmopolitan ) A Best Horror Book of 2023 ( Esquire ) A 2023 World Fantasy Award finalist Catriona Ward, author of The Last House on Needless Street , delivers a masterful story about friendship and betrayal, dark obsessions, and the impossibility of escaping your own story. "Here's your next obsession." (Kelly Link, author of The Book of Love ) In a cottage overlooking the windswept Maine coast, Wilder Harlow has begun the last book he will ever write. It is the story about the sun-drenched summer days of his youth in Whistler Bay, and the blood-stained path of the killer that stalked his small vacation town. About the terrible secret he and his companions, Nat and Harper, discovered entombed in the coves off the bay. And how the pact they swore that day echoed down the decades, forever shaping their lives. But the more Wilder writes, the less he trusts himself and his memory. He starts to see things that can't be real – notes hidden in the cabin, from an old friend now dead; a woman with dark hair drowning in the icy waters below, calling for help; entire chapters he doesn't recall typing, appearing overnight. Who, or what , is haunting Wilder? No longer able to trust his own eyes, Wilder begins to fear that this will not only be his last book, but the last thing he ever does. "Impossibly compelling, brilliantly plotted, and incredibly moving all at once." —Virginia Feito, author of Victorian Psycho At the Publisher's request, this title is being sold without Digital Rights Management Software (DRM) applied.